$λ$-Statistical Pointwise and Uniform Convergence of Sequences of Functions on Neutrosophic Normed Spaces - Hari Shankar; Ayaz Ahmad; Chandan Chaurasiya; Ayhan Esi (Sahand Communications in Mathematical Analysis)
This insightful article examines the $λ$-statistical convergence of function sequences within neutrosophic norm spaces. It introduces novel concepts such as $λ$-statistical pointwise convergence and $λ$-statistical uniform convergence specifically tailored for neutrosophic norm spaces, representing a notable advancement in the field. The article elucidates the foundational properties of these innovative concepts, offering valuable insights into their theoretical foundations and practical applications.